Pengaruh informasi keuangan dan non keuangan terhadap initial return ( studi pada perusahaan yang melakukan initial public offering di bursa efek Indonesia pada tahun 2006-2012) - Fenny Tria Putri; Restu Agusti; Al-azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to test the influence of financial information and non-financial to the initial return. The financial information in this regard can be divided into two such as financial leverage, EPS and non-financial information is divided into three namely company scale, underwriter reputation and the age of the company.In this study the population is the company that did the IPO, also known by the term IPO (Initial Public Offering) on the Indonesia stock exchange from 2006-2012. The sample are 70 companies selected by purposive sampling of companies that conduct the IPO at the Jakarta Stock ExchangeThe results showed that the variables of financial leverage, reputation of the underwriter and the age of company influential significantly to the initial return value with probability below 0.05. While the EPS and the scale of the company do not affect the initial return with more probabilities of 0.05. At 38,1% or 0,381 initial return can be explained by the variable financial leverage, EPS, the scale of the company, the underwriter reputation and age of the companies.Key Word: financial leverage, earning per share, company scale, underwriter reputation, age of he company, initial return.